PECULIARITIES OF STUTTERING IN PRESCHOOL CHILDREN (British Journal of Global Ecology and Sustainable Development, 2024)
In the article, the specific features of stuttering disorders in preschool children, emphasis in pronunciation, intonation, rhythm disorders, unfounded pauses in speech, prolongation with repetitions, sonority and rate of pronunciation, sound strength, height and Issues such as the change of fluency in connection with the speech goal and emotional state of the stutterer are covered.